2004
DOI: 10.3141/1878-10
|View full text |Cite
|
Sign up to set email alerts
|

Drivers' Perception of Pedestrians' Rights and Walking Environments

Abstract: A pedestrian and traffic safety study was conducted in San Diego County, California, with 1,587 adult and teenage traffic violators who were attending traffic school. The surveys were disaggregated on the basis of respondents' demographic characteristics. There were 589 Spanish speakers and 998 English speakers. The surveys measured respondents' safe driving score and correlated the score with their assessment of safety and the level of aggression shown toward pedestrians in six photographs. Photographs were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Previous studies have shown that drivers and pedestrians have limited knowledge of pedestrian right-of-way laws (5)(6)(7)(8). The research presented in this paper expands on these studies by considering driver and pedestrian knowledge of laws specifically related to marked and…”
Section: More Evidence Why Pedestrian and Driver Knowledge Of The Vehicle Code Should Not Be Assumedmentioning
confidence: 89%
“…Previous studies have shown that drivers and pedestrians have limited knowledge of pedestrian right-of-way laws (5)(6)(7)(8). The research presented in this paper expands on these studies by considering driver and pedestrian knowledge of laws specifically related to marked and…”
Section: More Evidence Why Pedestrian and Driver Knowledge Of The Vehicle Code Should Not Be Assumedmentioning
confidence: 89%
“…Physical characteristics of intersections were communicated by both descriptions (i.e., of speed), and images. Sarkar and Andreas (2004) used black and white photographs of drivers engaged in aggressive acts. These photographs clearly showed the vehicle, driver, and pedestrians in the vicinity of the vehicle.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Previous research of this nature has focused on the driver's perception of what pedestrians may find aggressive (e.g., Sarkar & Andreas, 2004) but currently there is no known study examining the pedestrian's perception of these aggressive behaviors. There is also no known study examining the effects of distraction on pedestrians from either the driver or the pedestrian perspective.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Another educational approach for enhancing child pedestrian safety is to educate drivers on safe operating behavior when pedestrians are present or expected. A recent study of California drivers found that few drivers were aware of traffic laws and etiquette relating to pedestrians, typically assuming that it was the pedestrian's responsibility to yield to the driver (81). As such, motorist education programs would appear to be a highly promising approach for enhancing pedestrian safety.…”
Section: Motorist Education Programsmentioning
confidence: 99%